P516 The use of first-line biologics in patients with ulcerative colitis in Norway from 2011 to 2016. (25th January 2019) - Anisdahl, K; Lirhus, S; Medhus, A; Buer, L; Melberg, H O; Moum, B; Lie Høivik, M
Abstract: Background: Treatment of ulcerative colitis (UC) is preference based and might also be affected by drug costs. In Norway, biosimilar infliximab entered the market in 2014 at a reduced cost of 40% compared with the original product. We have previously shown an increase in the use of biologics for inflammatory bowel disease (IBD) between 2011 and 2014. In the present study, we aimed to assess whether there was a change in the proportion of patients receiving biologics between 2011 and 2016 and if the preferred first-line biologic changed after the introduction of biosimilar infliximab. Methods: Data were collected from the Norwegian Patient Registry (NPR) and the Norwegian Prescription Database (NorPD). The study cohort was defined as all patients with at least two registered K51 (UC) within 1 year between 2011 and 2016. Patients were followed for 1 year after identification of first diagnosis code. The use of biologics is recorded with ATC codes for each patient in NPR and NorPD. The ATC codes do not distinguish between biosimilars and originators. Patients were stratified by the year of first diagnosis to examine change over time. Results: A total of 8264 patients were included in the study. The total use of biologics stratified by year is shown in Figure 1. The proportion of patients receiving biologics within 1 year of diagnosis increased significantly from 8.2% in 2011 to 15.1% in 2016 ( p < 0.0001). The proportion of patients receiving adalimumab as their first biologic after 1 year of diagnosis was 1.7% in 2011 compared with 0.4% in 2016. Opposed to this, the use of infliximab increased from 6.6% in 2011 to 13.6% in 2016. Conclusions: There was a significant increase in the proportion of patients who received biologics within the first year of diagnosis between 2011 and 2016. Infliximab was the preferred first-line biologic for UC both before and after 2014.